Sigma‐1 receptor attenuates osteoclastogenesis by promoting ER‐associated degradation of SERCA2 - Wei, Xiaoan; Zheng, Zeyu; Feng, Zhenhua; Zheng, Lin; Tao, Siyue; Zheng, Bingjie; Huang, Bao; Zhang, Xuyang; Liu, Junhui; Chen, Yilei; Zong, Wentian; Shan, Zhi; et al. (EMBO molecular medicine, 2022)
Sigma‐1 receptor (Sigmar1) is a specific chaperone located in the mitochondria‐associated endoplasmic reticulum membrane (MAM) and plays a role in several physiological processes. However, the role of Sigmar1 in bone homeostasis remains unknown. Here, we show that mice lacking Sigmar1 exhibited severe osteoporosis in an ovariectomized model. In contrast, overexpression of Sigmar1 locally alleviated the osteoporosis phenotype. Treatment with Sigmar1 agonists impaired both human and mice osteoclast formation in vitro . Mechanistically, SERCA2 was identified to interact with Sigmar1 based on the immunoprecipitation‐mass spectrum (IP‐MS) and co‐immunoprecipitation (co‐IP) assays, and Q615 of SERCA2 was confirmed to be the critical residue for their binding. Furthermore, Sigmar1 promoted SERCA2 degradation through Hrd1/Sel1L‐dependent ER‐associated degradation (ERAD). Ubiquitination of SERCA2 at K460 and K541 was responsible for its proteasomal degradation. Consequently, inhibition of SERCA2 impeded Sigmar1 deficiency enhanced osteoclastogenesis. Moreover, we found that dimemorfan, an FDA‐approved Sigmar1 agonist, effectively rescued bone mass in various established bone‐loss models. In conclusion, Sigmar1 is a negative regulator of osteoclastogenesis, and activation of Sigmar1 by dimemorfan may be a potential treatment for osteoporosis in clinical practice. Synopsis Activation of Sigma‐1 receptor by dimemorfan promoted SERCA2 degradation, causing reduction in osteoclast formation. Targeting Sigma‐1 receptor and dimemorfan may be a novel potential therapeutic approach for osteoporosis. Loss of Sigma‐1 receptor was found to cause severe osteoporosis phenotype compared with WT mice. Activation of Sigma‐1 receptor both in vivo and in vitro rescued bone loss models and suppressed osteoclast formation. SERCA2 was interacted with Sigma‐1 receptor and degraded in ERAD pathway, leading to impaired osteoclast's relative gene expression. Long term use of dimemorfan in clinical practice made it a promising drug towards osteoporosis treatment. Graphical Abstract Activation of Sigma‐1 receptor by dimemorfan promoted SERCA2 degradation, causing reduction in osteoclast formation. Targeting Sigma‐1 receptor and dimemorfan may be a novel potential therapeutic approach for osteoporosis.